2006
DOI: 10.2298/avb0606479f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding diet contaminated with deoxynivalenol on plasma chemistry in growing broiler chickens and the efficacy of glucomannan mycotoxin adsorbent

Abstract: The aim of this study was to evaluate effects of modified glucomannan (Mycosorb®) on plasma chemistry of broiler chicks after deoxynivalenol (DON) inclusion in the diet from hatching to 6 weeks of age. Three groups of broiler chicks were formed with 14 birds in each group. The three diets included control (0.2 ppm deoxynivalenol), deoxynivalenol-contaminated (3 ppm deoxynivalenol) and deoxynivalenol- contaminated (3 ppm deoxynivalenol) plus Mycosorb®(2 g/kg diet). After 6 weeks of feeding all birds were sacrif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
3
1
Order By: Relevance
“…The increased level of triglycerides might be related to lipid metabolism alteration and or to biliary obstruction [ 58 ]. These results are in contrast with the previous and actual findings which observed decreased cholesterol and triglycerides levels in broilers [ 19 , 27 , 64 , 68 , 89 , 90 ]. This is in agreement with the meta-analysis report of Andretta et al [ 94 ] indicating that broilers fed challenged mycotoxins (T2, FBs, DON, OTA, and ZEN) had lower total cholesterol (−14 %) and lower triglycerides (−39 %) compared to negative control birds.…”
Section: Biomarkers Of Effectcontrasting
confidence: 99%
See 2 more Smart Citations
“…The increased level of triglycerides might be related to lipid metabolism alteration and or to biliary obstruction [ 58 ]. These results are in contrast with the previous and actual findings which observed decreased cholesterol and triglycerides levels in broilers [ 19 , 27 , 64 , 68 , 89 , 90 ]. This is in agreement with the meta-analysis report of Andretta et al [ 94 ] indicating that broilers fed challenged mycotoxins (T2, FBs, DON, OTA, and ZEN) had lower total cholesterol (−14 %) and lower triglycerides (−39 %) compared to negative control birds.…”
Section: Biomarkers Of Effectcontrasting
confidence: 99%
“…Regarding biochemical parameters reflecting protein metabolism, it has been described that the total plasma protein and albumin levels of chickens fed a contaminated diet with 2.95 mg DON/kg feed during 2 weeks of exposure were decreased compared to control [ 88 ]. The reduction of total protein level after feeding DON to broilers was observed also in previous reports [ 27 , 89 , 90 ]. This decrease could be the result of protein and DNA synthesis inhibition induced by DON [ 14 ].…”
Section: Biomarkers Of Effectsupporting
confidence: 87%
See 1 more Smart Citation
“…In contrast, other research showed that a challenge by AFB1, ochratoxin, zearalenone and T-2 toxin reduced AST at 21 days but failed to characterize any significant impact when observed at 35 days [4]. Furthermore, a diet containing only the Fusarium mycotoxin DON at 3 mg/kg fed over 42 days did not impact measured blood metabolites [23]. Taking these trials into account, along with our current research, it may be concluded that AFB1 has a stronger influence on blood metabolites than Fusarium type mycotoxins, especially as AFB1 tends to target liver metabolism more strongly.…”
Section: Discussionmentioning
confidence: 80%
“…A similar effect of product inclusion was observed by Vartiainen et al [10], where broilers fed ochratoxin A (OTA) at 0.1 mg/kg feed had increased OTA deposition in the liver that was numerically lowered with inclusion of 2.0 kg/ton of the YCWE, and significantly reduced with inclusion of 4.0 kg/ton YCWE to the ration. Conversely, the inclusion of 0.2% glucomannan polymer to a turkey diet containing Fusarium mycotoxin over 21 days was enough to significantly improve duodenum villus height [23]. The researchers in the latter trial did not investigate an inclusion of 0.4%, so the difference between product inclusion cannot be determined in that case.…”
Section: Discussionmentioning
confidence: 99%